Nucleotide degradation and ribose salvage in yeast - Yi‐Fan Xu; Fabien Létisse; Farnaz Absalan; Wenyun Lu; Ekaterina Kuznetsova; Greg Brown; Amy A Caudy; Alexander F Yakunin; James R Broach; Joshua D Rabinowitz (Molecular Systems Biology)
Abstract Nucleotide degradation is a universal metabolic capability. Here we combine metabolomics, genetics and biochemistry to characterize the yeast pathway. Nutrient starvation, via PKA, AMPK/SNF1, and TOR, triggers autophagic breakdown of ribosomes into nucleotides. A protein not previously associated with nucleotide degradation, Phm8, converts nucleotide monophosphates into nucleosides. Downstream steps, which involve the purine nucleoside phosphorylase, Pnp1, and pyrimidine nucleoside hydrolase, Urh1, funnel ribose into the nonoxidative pentose phosphate pathway. During carbon starvation, the ribose‐derived carbon accumulates as sedoheptulose‐7‐phosphate, whose consumption by transaldolase is impaired due to depletion of transaldolase's other substrate, glyceraldehyde‐3‐phosphate. Oxidative stress increases glyceraldehyde‐3‐phosphate, resulting in rapid consumption of sedoheptulose‐7‐phosphate to make NADPH for antioxidant defense. Ablation of Phm8 or double deletion of Pnp1 and Urh1 prevent effective nucleotide salvage, resulting in metabolite depletion and impaired survival of starving yeast. Thus, ribose salvage provides means of surviving nutrient starvation and oxidative stress.